Pelatihan Manajemen Usaha Bagi Pengelola Kantin di Pondok Pesantren Manufa Sragi Kabupaten Pekalongan - Sunarko, Moh. Heru; Subagiyo, Muhamad (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
Business management helps business managers formulate clear business goals and plan steps to achieve them. With good business management, it can be easier for business managers to maximize existing resources. The purpose of this service is to provide training and education about business management for canteen managers at Manufa Islamic Boarding School. This service uses the Participatory Action Research (PAR) method. The results of this research are: (1) Business managers can understand the importance of business management. (2) Business managers can be more skilled in planning their canteen business activities. (3) Business managers are better able to manage employees effectively. (4) Business managers realize the importance of coordination in their canteen business. (5) Business managers become more skilled in evaluating the performance of their canteen business objectively and critically.